Knowledge, Attitudes, and Barriers Toward Research Among Medical Students of Karachi - Bilal, Muhammad (Cureus, 2019)
Introduction Our study was meant to assess the knowledge, attitude, and barriers towards research in medical students of Pakistan. By assessing the factors, we aim to increase the role of medical students in research, which will eventually help developing countries like Pakistan to achieve self-reliance in health care. Methods Undergraduate and postgraduate students of medicine, dentistry, and pharmacy schools of Dow University of Health Sciences, Karachi, were enrolled from February-March 2018 in a cross-sectional, descriptive study using questionnaires to provide details of the parameters of attitude to the knowledge of and barriers towards research for each individual. All data were coded for each of the parameters. Data analyses were performed by one-way analysis of variance (ANOVA)/Tukey and Student’s t-test, Pearson’s correlation, and Chi-squared tests. Results A total of 850 questionnaires were received. The overall mean scores of students on attitude, knowledge, and barriers were 69.27 ± 13.44, 70.39 ± 15.67, and 72.46 ± 13.46, respectively; 81.8% of students’ scores fell above the middle of the maximum score for knowledge, but 84.5% of attitude scores came in at below the middle of the maximum score. Undergraduate students had a more positive attitude to research than postgraduate students (69.20 ± 11.10 vs 64.23 ± 10.98; p = 0.002). Male students had a better attitude than females (72.97 ± 20.54 vs 67.09 ± 21.56; p = 0.010). Barriers highlighted by students most significantly included a lack of funding support and preference for instruction over research. Conclusion Students showed good knowledge of research, but their attitude was not up to the mark. The barriers highlighted suggest a need for a change in the strategies for research. Attention should be paid to inculcate research as part of the student curriculum and to make available incentives, information, and mentors to solve the problems most students face in the field of research.